Monitoring progress toward measles elimination by genetic diversity analysis of measles viruses in China 2009–2010. (28th February 2014) - Zhang, Y.; Wang, H.; Xu, S.; Mao, N.; Zhu, Z.; Shi, J.; Huang, G.; Liu, C.; Bo, F.; Feng, D.; Lu, P.; Liu, Y.; et al.
Abstract With the achievement of high coverage for routine immunization and supplementary immunization activities (SIAs), measles incidence in mainland China reached its lowest level in 2010. The proportion of measles cases in the vaccination‐targeted population decreased during 2007–2010 after the SIAs. More than 60% of measles cases were in adults or infants, especially in the coastal and eastern provinces during 2009 and 2010. A total 567 isolates of measles virus were obtained from clinical specimens from 27 of 31 provinces in mainland China during 2009 and 2010. Except for two vaccine‐associated cases, one genotype D4 strain, two genotype D9 strains, and four genotype D11 strains, the other 558 strains were genotype H1 cluster H1a. Genotype H1 has been the only endemic genotype detected in China since surveillance began in 1993. Only genotype H1 was found in mainland China during 1993–2008, except for one detection of genotype H2. More recently, multiple genotypes of imported measles were detected even with the background of endemic genetotype H1 viruses. Analysis of the 450‐nucleotide sequencing window of the measles virus N gene showed that the overall genetic diversity of the recent geneotype H1 strains decreased between 2008 and 2010. The lower genetic diversity of H1 strains suggested that enhanced vaccination may have reduced the co‐circulating lineages of endemic genotype H1 strains in mainland China.